PENGEMBANGAN PROGRAM PELATIHAN PEMBUATAN BAHAN AJAR BERBASIS AI UNTUK PENINGKATAN KOMPETENSI DIGITAL GURU DI LINGKUNGAN PERGURUAN MUHAMMADIYAH - Wahyudi, Endang; Suryadi, Ahmad (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This study aims to develop a training program for creating instructional materials based on Artificial Intelligence (AI) to enhance the digital competencies of teachers at Muhammadiyah Darul Arqom School, Cianjur. The research method employed is Research and Development (R&D) using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Media and content validation results showed an average score of 92 out of 100 (highly feasible) in terms of content quality, novelty, and usability of digital applications. The effectiveness of the training was evidenced by an increase in teachers’ understanding of AI tools such as Gamma App, Canva, and ChatGPT for developing open educational resources. The average pretest score of 61.2 increased to 83.7 in the posttest, with an N-Gain of 0.72 (high category). Participants also gave very positive feedback on the training. Therefore, the training program is considered feasible, practical, and effective in improving teachers’ digital competencies.